Evaluation of the in vitro effectiveness of Amitraz, Cypermethrin and Ivermectin on Bovicola ovis (Schrank, 1781) (Revista de Ciências Agroveterinárias, 2023)
Parasitic diseases caused by drug-resistant lice are causing a decline in the productivity of sheep herds in Northeast Brazil. The aim was to evaluate the "in vitro" efficacy of Amitraz 12.5%, Cypermethrin 15% and Ivermectin 0.5% on the louse Bovicola ovis (Schrank, 1781). B. ovis (Schrank, 1781) from sheep in Mossoró/RN were used in this evaluation. The tested drugs were diluted following the manufacturer's recommendations. Negative controls consisted of lice immersed in water and lice not subjected to any treatments, including water. Five repetitions were performed per group (treatment), totaling 625 lice randomly distributed in 25 plates. Analyzes were carried out at the Laboratory of Animal Parasitology (LPA) of the Universidade Federal Rural do Semi-Árido (UFERSA). Mortality was evaluated after 1, 3, 6, 24 and 48 hours after the beginning of the experiment. Data were expressed as mean values ± standard deviation (SPSS version 23.0) and statistical differences between experimental groups were obtained by Kruskal-Wallis and Friedman, with a significance level of 5%. Ivermectin showed better efficacy when compared to other treatments from 1 hour of observation and at times 3 and 6 hours. However, at 24 and 48 hours, Cypermethrin was equivalent to Ivermectin in efficacy. The other treatments obtained results equivalent to those obtained with the use of ivermectin in 1 and 3 hours of evaluation. The similarity of results between Amitraz and negative controls up to 6 hours stands out. Through the present study it was observed that Ivermectin can be an alternative for the control of B. ovis lice (SCHRANK 1781) in sheep.
Keywords: lice; small ruminants; pediculosis; drugs